Characteristics of Sardinella Smart Flavor based on Enzymatic Hydrolysis Using a Calotropin and Papain Combination - Witono, Yuli; Masahid, Ardiyan Dwi; Belgis, Maria; Nafi', Ahmad; Azkiyah, Lailatul; Wahyuni, Livia; Majid, Nur Ika Okta (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Sardinella lemuru is one type of fish with the highest population and the most widely caught fish in Indonesia. The protein content is very high, namely 17.8-20% contains various amino acids including glutamic acid, which can potentially be a smart flavor precursor. The research focuses on enzymatic smart flavor production by examining the effect of concentration and hydrolysis time of calotropin and papain combination on characteristics of the smart flavor produced and determining the best treatment to produce smart flavor. This research used two factors: the concentration of enzyme (3%, 4%, and 6% with a ratio of papain and calotropin of 70%: 30%) and hydrolysis time (1, 2, and 3 hours). The research showed that yield ranged from 50.15-50.69%; brightness 89.72-91.57; water 6.91-9.51%; soluble protein 1.13-1.56 mg/ml; antioxidant activity 48.40-54.47%; emulsion power 0.16-0.18 m2/g, emulsion stability 17.27-24.33 minutes; water holding capacity 83.44-89.27% and effectiveness 1.00 (enzyme 6% and time of hydrolysis 3 hours). The best treatment with effectiveness was Sardinella lemuru smart flavor (6% enzyme and 3 hours hydrolysis) with a yield 50.54%, brightness 89.72, water 6.91%, soluble protein 1.56 mg/ml, antioxidant activity 54.47%, emulsion power and stability 0.18 m2/g and 24.33 minutes, and water holding capacity 89.27%.